HipHop aus Österreich: Lokale Aspekte einer globalen Kultur - Dörfler-Trummer, Frederik (2021)
Topic of this book is the historical and musical analysis of the Austrian hip-hop scene and its local adaptation of the global phenomenon hip-hop. It provides a detailed and comprehensive illustration of Austrian hip-hop's history and delivers - through the help of musical analysis - insight into musical characteristics of hip-hop music. But not only general characteristics of the music and its dominant subgenres in Austria are demonstrated, one main aim of the research is to seek out possible "glocal" features in Austrian hip-hop music and set this local scene it into a global context.